THE ROLE OF KNOWLEDGE SHARING, TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) AND JOB SATISFACTION ISLAMIC SCHOOL TEACHERS - Mohzana Mohzana (Erudio Journal of Educational Innovation, 2022)
The purpose of this research is to analyze the relationship between transformational leadership on organizational citizenship behavior (OCB), transformational leadership on job satisfaction, job satisfaction on OCB, knowledge sharing on OCB, knowledge sharing on job satisfaction. online questionnaire via social media to respondents. The respondents of this study were 378 Islamic  teachers who were determined by simple random sampling. The questionnaire was designed using a Likert scale of 1 to 7. Analysis of research data used a structural equation model (SEM) with SmartPLS 3.0 software. The stages of data processing in this research are validity test, reliability test and hypothesis test. The independent variables of this research are the culture and commitment of sustainable schools; and the dependent variable is the performance of school employees. The results of this study are transformational leadership has a positive and significant effect on OCB, transformational leadership has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on OCB, knowledge sharing has a positive and significant effect on OCB, knowledge sharing has a positive and significant effect on job satisfaction Islamic  teacher.